1997
DOI: 10.1128/jvi.71.5.3734-3741.1997
|View full text |Cite
|
Sign up to set email alerts
|

Autologous and heterologous neutralizing antibody responses following initial seroconversion in human immunodeficiency virus type 1-infected individuals

Abstract: In the course of human immunodeficiency virus type 1 (HIV-1) infection, patients develop a strong and persistent immune response characterized by the production of HIV-specific antibodies. The aim of our study was to analyze the appearance of autologous and heterologous neutralizing antibodies in the sera of HIVinfected individuals. For this purpose, primary strains have been isolated from 18 HIV-1-infected subjects prior to seroconversion (in one case) or within 1 to 8 months after seroconversion. Sera, colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(63 citation statements)
references
References 66 publications
8
53
1
Order By: Relevance
“…The data presented above on heterologous neutralizing antibodies against primary HIV-1 isolates were consistent with those of others, showing that heterologous antibodies were detected at low frequency and titer [Moog et al, 1997;Pilgrim et al, 1997;Bongertz et al, 2001;Guevara et al, 2002]. However, a recent study of Thai samples found that the higher the titer of neutralizing antibodies, the lower the rate of mother to child transmission of HIV-1 [Barin et al, 2006].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data presented above on heterologous neutralizing antibodies against primary HIV-1 isolates were consistent with those of others, showing that heterologous antibodies were detected at low frequency and titer [Moog et al, 1997;Pilgrim et al, 1997;Bongertz et al, 2001;Guevara et al, 2002]. However, a recent study of Thai samples found that the higher the titer of neutralizing antibodies, the lower the rate of mother to child transmission of HIV-1 [Barin et al, 2006].…”
Section: Discussionsupporting
confidence: 89%
“…Although it is now generally regarded that T-cell adapted stains may not be relevant as a measure for in vivo neutralizing responses [Zolla-Pazner, 1996], most previous studies on heterologous neutralizing antibodies used laboratory-adapted HIV-1 strains, which have more accessible neutralization epitopes [Beddows et al, 1998], thus providing neutralization titers across a wide range. In contrast, heterologous or autologous neutralizing antibodies against primary HIV-1 isolates are always detected at a low frequency and level, leaving only a narrow range of titers for comparison [Moog et al, 1997;Pilgrim et al, 1997;Bongertz et al, 2001;Guevara et al, 2002]. For the sake of completeness, this study utilized both a laboratory-adapted strain, HIV-1 MN, and primary isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the production of antibodies is efficient and used as a marker for serological diagnosis of infection, most antibodies do not exert neutralizing activity against primary virus isolates. Antibodies with neutralizing capacity against primary isolates emerge relatively late after seroconversion (>1 year post-infection) when the neutralizing activity is monitored on primary lymphocytes, and their neutralization spectrum broadens in time, revealing a temporal evolution of the humoral immune response generating cross-reactive neutralizing antibodies [Moog et al, 1997;Nyambi et al, 1997]. A correlation between the appearance of neutralizing antibodies and a decrease in viral load has been observed [Lathey et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups have observed a discrepancy between the neutralization of primary isolates and cell line-adapted strains [Wrin et al, 1995;Mascola et al, 1996;Moore et al, 1996;Moog et al, 1997], namely, the primary isolates are more resistant to neutralization than their laboratory-adapted strains.…”
Section: Discussionmentioning
confidence: 99%